2022
DOI: 10.1021/acsaem.2c02528
|View full text |Cite
|
Sign up to set email alerts
|

Au-Doped PtAg Nanorod Array Electrodes for Proton-Exchange Membrane Fuel Cells

Abstract: One-dimensional Pt-based alloy nanostructures have been demonstrated as highly active and durable catalysts for an oxygen reduction reaction (ORR), which are the key to achieving the sustainability of proton-exchange membrane fuel cells (PEMFCs). However, the high difficulty in the fabrication of a practical catalyst electrode based on these nanostructures has limited their potential for PEMFC applications. In this work, we demonstrate a facile approach of Pt-alloy nanorod (NR) array gas diffusion electrodes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Among synthesis methods for producing supportless Ptbased nanostructures, wet chemical methods are appealing due to their simplicity, tunability, and potential scalability. For instance, formic acid reduction of H 2 PtCl 6 provides a facile method for growing 1D nanostructures such as nanowires and nanorods [197,198]. Such structures can be further improved through alloying with other metals.…”
Section: Supportless Catalyst Film Electrodesmentioning
confidence: 99%
“…Among synthesis methods for producing supportless Ptbased nanostructures, wet chemical methods are appealing due to their simplicity, tunability, and potential scalability. For instance, formic acid reduction of H 2 PtCl 6 provides a facile method for growing 1D nanostructures such as nanowires and nanorods [197,198]. Such structures can be further improved through alloying with other metals.…”
Section: Supportless Catalyst Film Electrodesmentioning
confidence: 99%
“…Pt and Ag have long been brought together in various combinations to use as an electrocatalyst in electrochemical applications. [6,13,14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] To show the importance of the change in the electronic structure of Pt, M. Liu et al synthesized carbonsupported Pt-Ag alloys, hollow alloy, and Ag@Pt core@shell NPs by galvanic replacement reaction and achieved the enhancement in ORR activity due to the downshift in the d-band center. [14] It has been shown that precise control of Pt shell thickness on the Ag core during synthesis provides tunability toward ORR activity.…”
Section: Direct 4ementioning
confidence: 99%
“…Hydrogen-fueled proton exchange membrane fuel cells (PEMFCs) have emerged as a promising sustainable energy conversion technology due to their high efficiency and low emissions and are expected to reduce dependence on fossil fuels. Among the various potential applications of PEMFCs, fuel-cell electric vehicles (FCEVs) have already reached the commercialization stage due to intensive research and development aimed at increasing PEMFC performance and durability. , However, the durability of the platinum (Pt) electrocatalyst and its support material still remains a major issue in developing the next generation of FCEVs. , Although Pt-based electrocatalysts have been extensively researched with the aim of enhancing the sluggish oxygen reduction reaction (ORR) and increasing durability, few studies have sought to overcome the dissolution and aggregation of Pt during long-term operation under harsh conditions. , Although carbon supports can provide a higher surface area for active ORR sites, a remaining challenge is corrosion of the carbon support during actual driving operation with frequent dramatic changes in operating conditions such as fuel starvation and repeated start-up/shut-down cycles during long-term use. Therefore, it is necessary to develop an electrocatalyst and support material that can meet both the high-performance and high durability requirements. Specifically, further research is needed to obtain a carbon support with high durability against start-up/shut-down cycles.…”
Section: Introductionmentioning
confidence: 99%